2014
DOI: 10.1111/ijd.12535
|View full text |Cite
|
Sign up to set email alerts
|

Antinuclear antibodies in atopic dermatitis: a cross‐sectional study on 346 children

Abstract: No significant differences were observed between AD and the control group, or between different subtypes of AD in ANA prevalence. In both groups, ANA frequency increased with age, but in patients with AD, ANA had a tendency to appear earlier. Therefore, active AD during the early years of life could dispose selected patients towards earlier development of systemic autoreactivity and stress the need for regular follow-up of patients with ANA-positive AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Understanding the contribution of IgE autoantibodies in the pathophysiology of atopic dermatitis, knowing the targets, and studying the correlation between auto-IgE and the severity of the disease will lead to the prompt diagnosis and individualized management of atopic dermatitis and possible autoimmune comorbidities [ 65 , 66 ].…”
Section: Extra-cutaneous Clinical Manifestationsmentioning
confidence: 99%
“…Understanding the contribution of IgE autoantibodies in the pathophysiology of atopic dermatitis, knowing the targets, and studying the correlation between auto-IgE and the severity of the disease will lead to the prompt diagnosis and individualized management of atopic dermatitis and possible autoimmune comorbidities [ 65 , 66 ].…”
Section: Extra-cutaneous Clinical Manifestationsmentioning
confidence: 99%
“…Autoreactivity may develop in early infancy [ 20 ] and atopy in early childhood may increase the development of autoimmune diseases later in life [ 20 , 26 , 28 ]. In a cross-sectional study including 346 children with active AD and 117 controls antinuclear antibodies (ANA) have been found in both groups, which increased with age [ 40 ]. Although not significantly different, in children with AD the ANA antibodies had a tendency to appear earlier, suggesting that active AD in early infancy can lead to earlier development of systemic autoreactivity [ 40 ].…”
Section: Ige Autoreactivity In Atopic Dermatitismentioning
confidence: 99%
“…Pooling data from these studies showed a significantly higher frequency of ANA positivity in AD patients (OR: 2.18, 95% [1.31–3.64}) [ 4 ]. The most recent study looking for the prevalence of ANA in children by immunofluorescence showed that ANA were detectable at a younger age in AD than in healthy controls [ 49 ]. Evidence of autoreactivity in AD is supported by an increased prevalence of autoreactive CD4+ and CD8+ T cells from the blood and the skin of AD patients [ 28 ].…”
Section: Atopic Dermatitis: a Multifactorial Pathogenesismentioning
confidence: 99%